TYPES OF COMPANIES’ MANAGEMENT BODIES UNDER LITHUANIAN LAW - Virginijus Bite; Gintare Jakuntaviciute (European Scientific Journal, ESJ, 2014)
The bankrupts and financial crisis of large-sized companies, which took place in Eastern Asia, USA, Europe and Australia between the middle of XX and beginning of the XXI centuries, stimulated to take a deeper look into the legal status of the members of the companies’ management bodies, because one of the main reasons which determined the bankrupts and financial crisis all over the world was bad faith, improper performance of duties and negligence of the members of the companies’ management bodies. Unfortunately, neither Lithuanian legal acts, nor case law, nor legal doctrine provide with clear understanding what is and should be attributed to the category of the companies’ management bodies. This implies the uncertainty problem regarding the persons to be applied by the liability standard of management body members. Therefore, the purpose of this study is to determine the types of companies’ management bodies under Lithuanian law. This objective will be reached by the analysis of the concept of the management body, presenting the corporate governance systems dominating over the world and identifying the content as well as the nature of management function performed by the management bodies. The research has shown that the management function comprises three functions, i.e. direction, representation and control; therefore, board of directors, supervisory council and the head of a company are deemed to be part of a category of management bodies.